The Influence Of Human Resource Competence And Motivation On The Performance Of Ulos Msmes In Tarutung, North Tapanuli Regency - Deni Sormin; Adelina Lubis; Ikbar Pratama; Ihsan Effendi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine how the influence of Human Resource Competence and Motivation on MSME Performance in Ulos MSMEs in Tarutung, North Tapanuli Regency. Quantitative research uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the SmartPLS 3.2.8 application to test the relationship between Human Resource Competence, Motivation and MSME Performance. This study uses primary data with data obtained using a research questionnaire. Respondents of Ulos MSME business actors in Tarutung were 100 respondents with a sampling technique using Slovin. Based on the results of the hypothesis test, Human Resource Competence has a positive effect on MSME Performance with a path coefficient of 0.508 and t-statistics of 6,448. Motivation has a positive effect on MSME Performance with a path coefficient of 0.262 and t-statistics of 2,964. So, it is concluded that there is a significant positive influence between human resource competence and motivation on the performance of MSMEs in Ulos MSMEs in Tarutung, North Tapanuli Regency.